Impurity screening behavior of the high-field side scrape-off layer in near-double-null configurations: prospect for mitigating plasma–material interactions on RF actuators and first-wall components. (24th May 2017) - LaBombard, B.; Kuang, A.Q.; Brunner, D.; Faust, I.; Mumgaard, R.; Reinke, M.L.; Terry, J.L.; Howard, N.; Hughes, J.W.; Chilenski, M.; Lin, Y.; Marmar, E.; et al.
Abstract: The impurity screening response of the high-field side (HFS) scrape-off layer (SOL) to localized nitrogen injection is investigated on Alcator C-Mod for magnetic equilibria spanning lower-single-null, double-null and upper-single-null configurations under otherwise identical plasma conditions. L-mode, EDA H-mode and I-mode discharges are investigated. HFS impurity screening is found to depend on magnetic flux balance and the direction of B   ×   ∇ B relative to the most active divertor. Impurity 'plume' emission patterns indicate that both parallel and perpendicular ( E   ×   B ) flows in the SOL contribute to the 'flushing' of impurities towards the active divertor, thereby affecting the overall impurity screening behavior. Despite the fact that the HFS SOL is extremely narrow in near-double-null configurations, this SOL is able to screen locally injected nitrogen at least as effectively as the low-field side (LFS) SOL—up to a factor of 10 more effective, depending on specific plasma conditions and whether the magnetic geometry produces parallel flows that work with or against E   ×   B flows. For situations in which the E   ×   B drift of the impurity ions opposes parallel flow toward the primary divertor, HFS impurity screening is found to be least effective. When E   ×   B drifts assist parallel flow toward the primary divertor, HFS impurity screening is found to be very effective. These data support the idea of placing RF actuators and close-fitting wall components on the HFS of the tokamak. With this configuration, near-double-null magnetic topologies may be used for active control of plasma parameters at the antenna/plasma interface for optimal RF coupling, mitigate the generation of local impurities from plasma–material interactions and, taking advantage of favorable plasma flows and good screening properties of the HFS SOL, further minimize the impact of wall-born impurity sources on the plasma core.